Shariah Screening methodologies: SAC-SC vs DJIM Comparative study and impact assessment on their performance - Mohamed Yassine Khouildi; Mohamed Bengana; Mounir Rakibi; Mohamed Redouane Riad; Suhaib Aldirchawi (Global Review of Islamic Economics and Business, 2017)
Purpose – The purpose of this paper is to compare between two screening methodologies in terms of applied methods and the impact assessment. Other than this the paper measures the performance of screened stocks in terms of risk & return and compare it to the conventional onesDesign/methodology/approach – The methods used are a combination of archival and bibliographic research based on some previously published articles. Also the papers use secondary data from published reports.Findings – The paper identifies the impact assessment of the screening methodologies and how investors will not sacrifice part of their returns in order to achieve their moral and ethical values.Originality/value – Many studies compared the two screening indices in term of methodologies; however this paper investigates and uses a quantitative analysis on the impact and performance of the screening methodologies. Furthermore it compares the stages of screening between Shariah Advisory Council of Securities commission (SAC-SC) and Dow Jones Islamic Market Index (DJIM)Keywords – screening, methodologies, impact assessmentPaper type – comparative case study